2017
DOI: 10.1111/1541-4337.12259
|View full text |Cite
|
Sign up to set email alerts
|

Protein Characteristics that Affect the Quality of Vital Wheat Gluten to be Used in Baking: A Review

Abstract: The use of vital wheat gluten in the baking industry and wheat flour mills aims to improve the rheological characteristics of flour considered unsuitable to obtain products such as sliced bread, French bread, high-fiber breads, and other products that require strong flours. To improve characteristics such as flour strength, dough mixing tolerance, and bread volume, vital wheat gluten is added to flour at levels that can vary from 2% to 10% (flour basis), with 5% being a commonly used dosage. However, the vital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(92 citation statements)
references
References 123 publications
(227 reference statements)
2
89
0
1
Order By: Relevance
“…The results reflected greater changes in hydrophobicity of PB1121 as compared to other varieties during parboiling (Table ). The hydrophobicity was dependent upon protein and AA content as reported by Ortolan and Steel (). The higher hydrophobicity of PMR than MR may be attributed to increased protein and AA, particularly tyrosine and phenylalanine.…”
Section: Resultsmentioning
confidence: 54%
“…The results reflected greater changes in hydrophobicity of PB1121 as compared to other varieties during parboiling (Table ). The hydrophobicity was dependent upon protein and AA content as reported by Ortolan and Steel (). The higher hydrophobicity of PMR than MR may be attributed to increased protein and AA, particularly tyrosine and phenylalanine.…”
Section: Resultsmentioning
confidence: 54%
“…reported that bread with low specific volume showed a disagreeable appearance to the consumer. According to Ortolan and Steel (2017), the ability of the proteins present in the flour to expand and retain the gas formed inside the dough of the bread occurs due to the ability of the gluten present in the wheat protein. These authors reported that animal proteins do not possess this characteristic.…”
Section: Specific Volumementioning
confidence: 99%
“…Bread made from wheat is a commonly consumed food around the world (Zafar et al., ). Gluten, the dough‐developing protein of wheat flour, is responsible for its unique structural forming properties (Ortolan & Steel, ). Although white wheat flour provides high baking quality, it has a high glycemic index (GI; Foster‐Powell, Holt, & Brand‐Miller, ).…”
Section: Introductionmentioning
confidence: 99%